NAVIGATING CHRONIC HYPERTROPHIC RHINITIS: CAUSES, SYMPTOMS, AND TREATMENT STRATEGIES - Sanjar Usmonov; Khondamir Jurayev (Web of Journals Publishing, 2023)
Difficulty in nasal breathing contributes to the onset of numerous acute and chronic respiratory conditions affecting both the upper and lower respiratory tracts. Among the prevalent causes of this impediment lies hypertrophy of the nasal concha. Understanding the origins of concha hypertrophy and employing appropriate drug therapies or, when essential, surgical interventions becomes pivotal in averting both immediate and delayed complications. This article delves into the complexities of chronic hypertrophic rhinitis, detailing its origins, pervasive symptoms, and a spectrum of treatment modalities encompassing pharmaceutical and surgical approaches. Offering insights for professionals and individuals seeking comprehensive guidance, this document serves as an invaluable resource in understanding, addressing, and managing chronic hypertrophic rhinitis effectively.
Keywords: Rhinitis, Hypertrophy, Shell, Hyperplasia, Paranasal sinus.